Facile access to a Ge(II) dication stabilized by isocyanides - Swamy, V. S. V. S. N.; Yadav, Sandeep; Pal, Shiv; Das, Tamal; Vanka, Kumar; Sen, Sakya S. (Chemical Communications, 2016)
Herein, we introduce isocyanide as a ligand in main group chemistry and describe the facile isolation of a Ge(II) dication. The reaction of 2,6-dimethylphenylisocyanide with GeCl2 leads to the formation of a Ge(II) dication with two [GeCl3](-) molecules as counter anions. The dicationic Ge(II) center is bound to four isocyanide ligands and also holds a lone pair of electrons. DFT calculations reveal that the dication is stabilized only by sigma-donation from the four isocyanide ligands. Natural population analysis gives a charge of +0.74 on the Ge(II) center, indicating that the positive charge is shared by the isocyanide substituents.

Five concomitant polymorphs of a green fluorescent protein chromophore (GFPc) analogue: understanding variations in photoluminescence with pi-stacking interactions - Mali, Bhupendra P.; Dash, Soumya Ranjan; Nikam, Shrikant B.; Puthuvakkal, Anisha; Vanka, Kumar; Manoj, Kochunnoonny; Gonnade, Rajesh G. (Acta Crystallographica Section B-Structural Science Crystal Engineering and Materials, 2020)
The synthetically modified green fluorescent protein chromophore analogue 3,4,5-trimethoxybenzylidene imidazolinone (1) yielded five polymorphs (I, II, III, IV, V) concomitantly irrespective of the solvent used for crystallization. The pentamorphic modification of 1 is solely due to the interplay of iso-energetic weak intermolecular interactions in molecular associations as well as the conformational flexibility offered by a C-C single bond, which connects the electron-deficient moiety imidazolinone with the electron-rich trimethoxybenzylidene group. A common structural feature observed in all the polymorphs is the formation of a `zero-dimensional' centrosymmetric dimeric unit through a short and linear C-H center dot center dot center dot O hydrogen bond engaging phenyl C-H and imidazolinone carbonyl oxygen. However, the networking of these dimeric units showed a subtle difference in all the polymorphs. The 2D isostructurality was observed between polymorphs I, II and III, while the other two polymorphs IV and V revealed only `zero-dimensional' isostructurality. The different fluorescence emissions of Form I (blue) and Forms II to V (yellow) were attributed to the differences in pi-stacking interactions. It shows that one can modulate the photophysical properties of these smart materials by slightly altering their crystal structure. Such an approach will aid in developing new multi-colour organic fluorescent materials of varying crystal structures for live-cell imaging and fluorescent sensing applications.
Keywords: green fluorescent protein; hydrogen bonds; isostructurality; photoluminescence; pi-stacking; Polymorphs

Far-red active unsymmetrical squaraine dyes containing N-arylated indoline donors for dye sensitized solar cells - Jadhav, Avinash P.; Singh, Ambarish Kumar; Pandya, Rinu; Vanka, Kumar; Krishnamoorthy, Kothandam; Jayaraj, Nithyanandhan (Photochemistry and Photobiology, 2024)
Squaraine dyes possess sharp far-red active transition with high extinction coefficient and form aggregates on TiO2 surface. Aggregation of dyes on TiO2 has been considered as a detrimental factor for DSSC device performance, which can be controlled by appending alkyl groups to the dye structures. Hence by integrating alkylated (alkyl groups with both in-plane and out-of-plane) aryl group with indoline moiety to make it compatible with other electrolytes and for controlling the dye-aggregation, a series of squaraine acceptor-based dyes SQA4-6 have been designed and synthesized. SQA4-6 dyes showed absorption between 642 and 653 nm (lambda max), photophysical and electrochemical studies indicated that the HOMO energy levels of this sets of dyes are well aligned with the potentials of I-/I3-\$\$ {\textbackslashmathrm{I}}_3<\^>{-} \$\$ and [Co(bpy)3]2+/3+ redox shuttles for better dye regeneration process. DSSC device efficiency of 3% has been achieved for SQA5 dye with iodolyte (I-/I3-\$\$ {\textbackslashmathrm{I}}_3<\^>{-} \$\$) electrolyte in the presence of 0.3 mM of chenodeoxycholic acid (CDCA). The IPCE profile of DSSC device fabricated with SQA4-6 dyes indicated the contribution of aggregated structures for the photocurrent generation. Dye-sensitized solar cell (DSSC) device efficiency of 3% (Jsc 5.72 mA cm-2, Voc 662 mV and ff 79%) has been achieved for an unsymmetrical squaraine dye, SQA5 with iodolyte electrolyte and the incident photon to current efficiency (IPCE) profile indicates the contribution of aggregated structures for the photocurrent generation.*image
Keywords: aggregation of dye; arylation on N-atom of indoline donor; dye-sensitized solar cell; squaraine dye

From Delocalization to Disruption: The Role of Aromaticity in N-Heterocyclic Carbenes' Reactions with Diazoalkane and Diazoester - Sharma, Himanshu; Fernandez, Israel; Vanka, Kumar (Journal of Organic Chemistry, 2025)
Aromaticity is a fundamental force shaping molecular stability and reactivity, yet its dynamic role along reaction coordinates remains poorly understood. In this study, we unveil how dynamic changes in aromatic character govern the reactivity of 5-ItBu with diazoalkanes and diazoesters through a multifaceted computational approach. By integrating electronic, magnetic, structural, and energetic aromaticity descriptors, we demonstrate that the retention of aromaticity along the reaction path markedly lowers activation barriers, while its disruption imposes significant energetic penalties. Activation strain model (ASM) and energy decomposition analysis (EDA) further underscore the role of aromatic stabilization in enhancing orbital interactions that drive reactivity. These insights establish a cohesive mechanistic framework, highlighting aromaticity not merely as a static structural feature but as a tunable lever in the design of selective transformations and next-generation catalysts.